Synthesis, X-ray crystallography, spectroelectrochemistry and computational studies on potential copper-based radiopharmaceuticals - Holland, J; Barnard, P; Collison, D; Dilworth, JR; Edge, R; Green, J; Heslop, J; McInnes, E; Salzmann, C; Thompson, A (2008)
The synthesis of metal(II) complexes of a bis(thiosemicarbazonato) ligand derived from 1,2-cyclohexanedione are reported. The compounds have been characterised by a range of techniques including reverse-phase HPLC, cyclic voltammetry, NMR, UV/Vis, IR, Raman and EPR spectroscopy. X-ray crystal structures of the proligand and two copper(II) complexes have been obtained, and the electronic structures have been analysed by using DFT calculations. DFT calculations have also been used to map the potential energy surface of a related bis(thiosemicarbazone) proligand and predict solution-phase one-electron reduction potentials of the copper(II) complex by using three polarisable continuum solvation models. Electrochemistry experiments show that the copper(II) complex undergoes quasi-reversible one-electron reduction at biologically accessible potentials and is within the range proposed for the complex to be hypoxia-selective. In addition, UV/Vis spectroelectrochemistry experiments have been used to characterise the reduced copper(I) anion, and the reaction between the anion and dioxygen has been characterised by experiments and theory. Observation of this oxidation reaction has important implications for the proposed mechanisms of hypoxia selectivity of bis(thiosemicarbazonato) copper(II) complexes. The copper-64 radiolabelled complex has been prepared in aqueous solution which demonstrates the potential of use of these complexes as medical imaging agents. © Wiley-VCH Verlag GmbH and Co. KGaA, 2008.